(untitled) (Journal of Armed Forces Medical College, Bangladesh, 2026)
Background: Oligohydramnios is defined where the amniotic fluid index below the 5th centile for gestational age. This can occur 1-5% of all pregnancies, it rises more than 12% in post term pregnancies worldwide. It is associated with adverse perinatal outcome like foetal lung hypoplasia, foetal limb deformities-potters syndrome and preterm delivery, foetal growth restriction and foetal renal congenital anomalies. Objective: To study the outcome of pregnancies with severe oligohydramnios (AFI <5cm) at or beyond 37 weeks. Methods: This is a prospective observational study conducted over the course of 6 months from August 2022 to January 2023 in the Department of Obstetrics and Gynaecology in Combined Millitary Hospital (CMH), Dhaka, Bangladesh. Pregnant women at term (≥37 weeks) with oligohydramnios diagnosed on ultrasound were included. Data were collected from both maternal and foetal medical records. Maternal data included age, parity, gestational age, medical history and mode of delivery. Foetal data included birth weight, APGAR score, IUGR, presence of congenital anomalies and admission to the neonatal intensive care unit (NICU). Ultrasonographic parameter including amniotic fluid index was also recorded. Informed consent was obtained from all participants before enrollment. The sample size was calculated using a formula for a single proportion. Based on previous studies, we assumed that the incidence of adverse outcomes in term pregnancies complicated by oligohydramnios was around 1-5%. With an alpha error of 0.05 and a power of 0.80, a minimum sample size of 100 women was required. Results: The majority of women (50%) were nulliparous, and the mean maternal age at the time of delivery was 22.3±0.9 years. The most common mode of delivery was caesarean section (81%). The majority birth weight (73%) was >2.5 kg, and the mean APGAR score at 5 minutes was 8.2±1.1. The associated IUGR were 38% cases, congenital anomalies were present only in 2% of cases. Forty-seven neonates (47%) required admission to the NICU and no neonatal deaths were reported. Conlcusion: Oligohydramnios is associated with foetal and neonatal death which may related to underlying cause of oligohydramnios or sequelae of reduced amniotic fluid volume or both. JAFMC Bangladesh, Vol 21, No 2 (December) 2025:40-43